Analisis Prosedur Sistem Pembayaran Dana Pensiun Pada PT TASPEN (Persero) KCU Medan - Mutiara Lubis; Muhammad Arif (Lembaga Pengembangan Kinerja Dosen, 2023)
Analysis of Pension Fund Payment System Procedures at PT Taspen (Persero) KCU Medan. This research aims to find out how the pension fund payment system is at PT Taspen (Persero) KCU Medan. This research is included in survey research using a qualitative research approach. The subject of this research is PT Taspen (Persero) KCU Medan. The research method used in data collection was interviews, observation and documentation. The results of this research show that the PT Taspen (Persero) KCU Medan pension fund payment system uses a pay as you go system by implementing two payment techniques, namely manual and Automatic Klim Services. The Automatic Klim service will make it easier to access pension payment claim applications, which are integrated by agencies or BKD. Completeness of administrative requirements will facilitate the process of paying pension funds. Through a claim application, either manual or automatic claim, that meets the requirements for salary payments, payments can be made either directly or by transfer. Retirement is one of the awards given to Civil Servants (PNS) for their services to the State. Procedures are guidelines and implementation of work which consists of continuous work step by step so that it is a form of collaboration between one part and another.